An Optimal Effect Of Overload And Unbalanced Load On Transformer Lifetime In 20kv Distribution Substation - Rian Trinobeth Purba; Apda Eriansyah; Alfiansyah, Alfiansyah; Krisyanto Satria Habeahan; Solly Aryza (Sean Institute, 2025)
This study aims to analyze the effect of overload and load imbalance on the service life of transformers in 20 kV distribution substations. Distribution transformers function vitally in the power distribution system, but often face problems such as overload and load imbalance that can affect their performance. The research method used is a quantitative approach with field measurements, focusing on evaluating transformer loading conditions. The measurement results show that the transformer operates at an overload with a loading percentage reaching 109.8%, and a load imbalance of 19.16%. These findings indicate that these conditions can cause an increase in operating temperature, damage insulation, and shorten the life of the transformer. The combination of overload and load imbalance accelerates transformer damage and reduces its reliability, which ultimately has a negative impact on the continuity of electricity supply to consumers. This study recommends the importance of effective load monitoring and management to maintain transformer performance and improve the quality of electricity supply. The results of this study are expected to provide insight for distribution system managers in an effort to improve the efficiency and operational reliability of distribution transformers.